2012
DOI: 10.3892/ijo.2012.1331
|View full text |Cite
|
Sign up to set email alerts
|

Puerarin suppresses production of nitric oxide and inducible nitric oxide synthase in lipopolysaccharide-induced N9 microglial cells through regulating MAPK phosphorylation, O-GlcNAcylation and NF-κB translocation

Abstract: Abstract. Microglial cells play a critical role in mediating central nervous system inflammatory processes. Activated microglial cells induced by proinflammatory factor, such as lipopolysaccharide (LPS), release many kinds of neurotoxic cytokines including reactive oxygen species (ROS) which contributes to the pathogenesis of neurodegenerative diseases. Puerarin, extracted from kudzu root, possesses the characteristic of neuroprotection, antioxidation and anticancer. In the present study, we observed that LPS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Moreover, OGT plays a key role in the inflammatory responses of macrophages. It has been observed that in N9 microglial cells, in response to LPS, the enhanced expression of iNOS, NO and ROS is mediated via the downregulation of OGT and protein O-GlcNAcylation, or via the upregulation of MAPKs phosphorylation and NF-κB translocation (101). In addition, overexpression of OGT exhibits inhibitory effects on the LPS-driven activation of NF-κB and iNOS through modulation of histone acetylation either directly or indirectly (102).…”
Section: Anti-inflammatory Role Of O-glcnacylationmentioning
confidence: 99%
“…Moreover, OGT plays a key role in the inflammatory responses of macrophages. It has been observed that in N9 microglial cells, in response to LPS, the enhanced expression of iNOS, NO and ROS is mediated via the downregulation of OGT and protein O-GlcNAcylation, or via the upregulation of MAPKs phosphorylation and NF-κB translocation (101). In addition, overexpression of OGT exhibits inhibitory effects on the LPS-driven activation of NF-κB and iNOS through modulation of histone acetylation either directly or indirectly (102).…”
Section: Anti-inflammatory Role Of O-glcnacylationmentioning
confidence: 99%
“…In a latest study by Li et al, treatment with puerarin to 6-OHDA-lesioned rats was observed to significantly increase the protein expression of DJ-1 and superoxide dismutase-2 in the SN [88]. In recent report by Zheng et al, puerarin was found to suppress LPS-induced release of iNOS and phosphorylation of MAPKs in N9 cells [89]. Similar in vitro effects of puerarin are also evident in 6-OHDA-induced neurotoxicity to PC12 cells, wherein puerarin inhibits the MPP + -induced phosphorylation of JNK [90].…”
Section: Neuroprotective Activity Of Bioactive Compounds From Herbmentioning
confidence: 99%
“…Puerarin ( 22 ) was also reported to prevent the dysfunction of the proteasomal system thus preventing the accumulation of conjugated proteins [ 209 ]. It was shown to suppress the LPS-induced release of iNOS and phosphorylation of MAPKs in N9 cells [ 210 ] and inhibits the MPP+-induced phosphorylation of JNK [ 211 ]. In 6-OHDA-lesioned rats, 23 significantly increased the protein expression of DJ-1 and SOD-2 in the substantia nigra [ 212 ] and increased the expression of the glial cell-derived neurotrophic factor in the striatum of rats administered with 6-OHDA [ 213 ].…”
Section: Classical Examples Of Neuroprotective Drugs Of Plant-origmentioning
confidence: 99%